INHERITANCE OF MORPHOLOGICAL CHARACTERS IN PIGEONPEA - D. R. SAPKAL,; A. N. PATIL,; V. R. SAPKAL,; M. P. MESHRAM,; M. P. GADEKAR, (The Bioscan, 2014)
Detection of assortment, selection of pure strains, mechanized crop production and proficient management practices in commercial varieties in pigonpea is generally based on growth habit, plant height and seed coat color as they are the expedient traits. In the present investigation inheritance of growth habit, plant height and seed coat color was studied with seven populations (parents, F2 , reciprocal, F2 and both back cross) of eight, ten and two crosses with respective characters. Data analysis of segregating populations (F2s and test crosses) was carried out with the help of chi-square test. Results showed that indeterminate growth habit, tall plant height and brown seed coat color was dominant over determinate, dwarf and cream white seed coat color respectively. No reciprocal differences were observed, indicating no material effect to govern the traits. Over the F2 families, 2244 plants were indeterminate and 723 were determinate,2666 were tall plant type and 945 were dwarf type and also 481 plants were brown seeded and 144 plants were cream white, fitting the overall segregation into a well fit of 3:1 ratio with P –value 0.44,0.10 and 0.27 respectively.F2 inheritance study showed that all traits were governed by single gene and it was confirmed with the help of test cross progenies as its segregated and well fitted 1:1 ratio. All traits being monogenic, the expression of these visible markers are independent of environment and therefore, can be incorporated effectively as a marker in pigeonpea genome. A genetic inheritance study is essential for transferring these traits in productive pigeonpea background.